The role of autonomy as a predictor of entrepreneurial intention among university students in Yemen - Al-Jubari, Ibrahim; Hassan, Arif; Hashim, Junaidah (Inderscience Enterprises Ltd., 2017)
Autonomy is one of the most valued motives by entrepreneurs. However, it has been rather less emphasised in entrepreneurship research. Therefore, the main objective of the present study is to examine the role of autonomy in fostering entrepreneurial attitudes and intention. Drawing on theory of planned behaviour, the relationships between autonomy and intention directly and via mediators were examined. Data were obtained from 622 undergraduate students using standardised instruments. Structural equation modelling was used to test the hypothesised model and structural relationships. The findings emphasise the relevance and importance of autonomy. It is found that autonomy is an influential predictor of entrepreneurial intention, but not directly, rather through its proximal determinants and the autonomy-intention relationship is fully mediated by attitude, subjective norms and perceived behavioural control. The present study contributes to body of knowledge of entrepreneurial intention by extending theory of planned behaviour model and incorporating one of the most valued motivational determinants namely autonomy. Copyright